IRA Teknik Consulting Engineers / Nur Nadia Ashari - Ashari, Nur Nadia (UiTM Cawangan Johor Kampus Pasir Gudang, 2014)
The construction have many company to involve before the building finish. The company that involves are mechanical and electrical, civil and structure, architect, planner, interior design and contractor. Mechanical and electrical function for the design the follow of current, make the wire safe from human, and connect the Bomba detected. Civil and structure, design for the manhole of sewerage must submit the WK (Indah Water Konsortium). Design the drainage calculation invert level. Design the rainfall intensity, design structure such as roof, piling for column and pipe of sewerage.